Phylogenetic perspectives on diversification and character evolution in the species-rich genus Erysimum (Erysimeae; Brassicaceae) based on a densely sampled ITS approach - Moazzeni, Hamid; Zarre, Shahin; Pfeil, Bernard E.; Bertrand, Yann J. K.; German, Dmitry; Al-Shehbaz, Ihsan A.; Mummenhoff, Klaus; Oxelman, Bengt (Botanical journal of the Linnean Society, 2014)
Abstract. Erysimum includes 150-350 species distributed in the Northern Hemisphere, with Eurasia being the centre of greatest diversity. It is well known for i
Gesehen am 07.09.2020